Folk-story telling among the Shona and Freire's framework of banking versus dialogical methods of education – In search of innovation and social cohesion in post-independence Zimbabwe's education - Charamba, T; Mutasa, Davie E (Taylor & Francis, 2021)
Freire established what he termed the banking method of education versus the dialogical method of education. He argues that the former should be discouraged since it kills interaction between the teacher and the learner and encourages learning by rote. Dialogical education, on the other hand, should be promoted in educational circles since it activates participatory learning and curtails rote learning. This article discusses how the art of folk-story telling discouraged banking methods of teaching and promoted dialogical education in Shona traditional societies. This is contrasted with the modern (i.e. colonial and post-independence) Zimbabwean formal education system which promotes banking methods of teaching folktales at the expense of dialogical methods. Recommendations are made through which the use of dialogical education in the teaching of folktales in schools can be promoted. The article concludes that there is a need for educational reform in Zimbabwe that is aimed at revamping the pedagogy of teaching folktales in schools. If schools adopt the right attitude and commit themselves to such an exercise, Zimbabweans will oust the use of banking approaches to the teaching of folktales in schools in favour of dialogical approaches. The researchers have used document analysis, participation and observation, and in-depth personal interviews to gather data for this research.